Frequent accelerated idioventricular rhythm in an otherwise healthy child: a case report and review of literature - Daria Ljubas Perčić; Nikola Krmek; Ivica Benko; Hrvoje Kniewald; Suzana Bitanga; Matej Katavić; Marko Perčić (BMC Cardiovascular Disorders, 2023)
Abstract Background Accelerated idioventricular rhythm (AIVR) is a wide QRS complex dysrhythmia that, as far as pediatric population is concerned, occurs mostly in children with underlying systemic or heart disease. Its clinical course is thought to be typically benign in otherwise healthy children and treatment to be completely needless. Existing guidelines/recommendations are based entirely on cases that had low daily burden of AIVR, and those referring to treatment itself are very unspecific. Pharmacologic therapy has been mostly unsuccessful and catheter ablation as a way of treatment has been only sporadically reported. This article is a case report with a literature review that aims to practically separate the age groups into newborn and older children and to emphasize the different clinical outcomes of children with occasional and frequent AIVR. There are only a few cases so far describing undesirable outcomes of this condition, and most of these patients had high daily burden of AIVR. To be more specific, among 38 healthy children older than 1 year reported in total, 6 had undesirable outcomes, short-term in terms of developing malignant arrhythmia or long-term in terms of developing cardiomyopathy/heart failure. Case presentation An 11-year-old boy had been referred to our center for a workup of incidentally discovered wide-complex arrhythmia. He was asymptomatic, with no underlying cardiac or systemic diseases. Continuous heart rate monitoring detected AIVR during most time of monitoring. In 24-h Holter-ECG, wide QRS complexes accounted for 73%. With parental consent, we conducted an electrophysiological study accompanied by radiofrequent ablation of ectopic focus, which lead to an instantaneous sinus rhythm that continued during the entire follow-up. Conclusion AIVR is a rare dysrhythmia in the pediatric population, typically considered benign. Nevertheless, more than a few cases evidence its harmful potential, short-term in terms of developing malignant arrhythmia or long-term in terms of developing cardiomyopathy. Gathering more knowledge and experience along with conducting further studies is essential for the enhancement of understanding this condition, and selecting potentially vulnerable patients as well as their treatment.